A moderating role of HR analytics between employee engagement, retention and organisational performance. (8th September 2022) - Muhammad, Ghulam; Naz, Farah
The emerging benefits of HR analytics force the firm to pursue its implementation in the processes or activities related to HR department for the smooth as well as better management of employees that drives superior organisational value. The purpose behind the conduction of this study is to examine the moderating efficacy of HR analytics on the relationship between employee engagement, employee retention and the performance level of the banking sector of Karachi, Pakistan. The data were collected from 120 HR professionals from banking sector and analysed by using Smart PLS 3.2.8. The results of this study disclosed that the effective implementation of retention strategies is critical for enhancing organisational outcomes. Furthermore, it is also analysing that with the help of HR analytics, firms can make their employees more engaged and ameliorate their performance level. After analysing the results, managerial implications have been suggested to the management of banks.